Pengaruh E-Commerce Terhadap Minat Beli Konsumen Pada Produk Sayuran Di Kota Banda Aceh - Faisal Faisal; Indra Indra; Romano Romano (Jurnal Ilmiah Mahasiswa Pertanian, 2020)
Abstrak. Perkembangan teknologi informasi akhir-akhir ini terus mengalami kemajuan. Ditandai dengan bertambahnya pengguna internet dikalangan masyarakat berdasarkan data dari Asosiasi Penyelenggara Jasa Internet Indonesia (APJII), pada tahun 2017 pengguna internet di Indonesia sebesar 143 juta jiwa dan pada tahun 2018 meningkat secara signifikan sebesar 171 juta jiwa dari total populasi penduduk sebesar 264 juta jiwa. Hal tersebut tentu menjadi peluang besar bagi pelaku bisnis online atau dikenal dengan e-commerce. Semakin maraknya kehadiran bisnis online ini semakin banyak pula produk-produk yang dipasarkan salah satunya adalah produk sayuran. Kehadiran sistem jual beli online pada produk sayuran guna untuk mempermudah masyarakat dalam memenuhi kebutuhan sayur dirumah tanpa harus berbelanja ke pasar, sehingga dipercaya dapat menumbuhkan minat seseorang untuk membeli produk tersebut. Namun dilain sisi berdasarkan data dari Badan Pusat Statistik di Provinsi aceh masyarakatnya masih sangat kurang mengkonsumsi sayur-sayuran khususnya di daerah perkotaan.   Tujuan penelitian adalah untuk mengetahui pengaruh dari e-commerce terhadap minat beli pada produk sayuran di Kota Banda Aceh. Penelitian ini dilakukan pada bulan Januari tahun 2020 di Kota Banda Aceh. Sampel yang digunakan sebanyak 100 orang konsumen sayuran online. Metode analisis yang digunakan adalah  uji chi-square untuk mengukur pengaruh setiap variabel.   Secara keseluruhan dapat disimpulkan bahwa berdasarkan hasil uji chi-square dengan menggunakan SPSS pada variabel e-commerce diperoleh nilai chi-square sebesar 16.309 dan p-value 0.001 0,05 maka terdapat pengaruh antara variabel e-commerce terhadap minat beli pada produk sayuran di Kota Banda Aceh. Selanjutnya pengukuran terhadap indikator variabel e-commerce yaitu kualitas sistem, kualitas informasi dan kualitas pelayanan juga menggunakan analisis uji-square, sehingga diperoleh hasil bahwa pada kualitas sistem berpengaruh nyata terhadap minat beli pada produk sayuran, pada kualitas informasi tidak berpengaruh nyata terhadap minat beli pada produk sayuran dan pada kualitas pelayanan berpengaruh nyata terhadap minat beli pada produk sayuran di Kota Banda Aceh.E-COMMERCE EFFECT ON CONSUMER BUYING INTEREST IN VEGETABLE PRODUCTS IN BANDA ACEH CITYAbstract.The development of information technology has recently continued to progress. Marked by the increase in internet users among the public based on data from the Indonesian Internet Service Providers Association (APJII), in 2017 internet users in Indonesia amounted to 143 million people and in 2018 increased significantly by 171 million from a total population of 264 million. This is certainly a great opportunity for online business people, known as e-commerce.The increasing presence of this online business, the more products being marketed, one of which is vegetable products. The presence of an online buying and selling system for vegetable products is in order to make it easier for people to fulfill their vegetable needs at home without having to shop at the market, so it is believed that it can increase someone's interest in buying these products. However, on the other hand, based on data from the Central Bureau of Statistics in Aceh Province, the people still consume very little amount of vegetables, especially in urban areas.      The research objective was to determine the effect of e-commerce on buying interest of vegetable products in the city of Banda Aceh. This research was conducted in January 2020 in the City of Banda Aceh. The sample used was 100 online vegetable consumers. The analytical method used is the chi-square test to measure the effect of each variable.                Overall it can be concluded that based on the results of the chi-square test using SPSS on the e-commerce variable obtained a chi-square value of 16,309 and a p-value of 0.001 0.05, so there is an influence between e-commerce variables on purchasing interest in vegetable products in Banda Aceh City. Furthermore, the measurement of the e-commerce variable indicators, namely system quality, information quality and service quality also uses square-test analysis, so that the results show that the quality of the system has a significant effect on buying interest of vegetable products, the quality of information has no significant effect on buying interest of Vegetable products and service quality have a significant effect on buying interest in vegetable products in Banda Aceh City.  Abstract. The development of information technology has recently continued to progress. Marked by the increase in internet users among the public based on data from the Indonesian Internet Service Providers Association (APJII), in 2017 internet users in Indonesia amounted to 143 million people and in 2018 increased significantly by 171 million from a total population of 264 million. This is certainly a great opportunity for online business people, known as e-commerce.The increasing presence of this online business, the more products being marketed, one of which is vegetable products. The presence of an online buying and selling system for vegetable products is in order to make it easier for people to fulfill their vegetable needs at home without having to shop at the market, so it is believed that it can increase someone's interest in buying these products. However, on the other hand, based on data from the Central Bureau of Statistics in Aceh Province, the people still consume very little amount of vegetables, especially in urban areas.                    The research objective was to determine the effect of e-commerce on buying interest of vegetable products in the city of Banda Aceh. This research was conducted in January 2020 in the City of Banda Aceh. The sample used was 100 online vegetable consumers. The analytical method used is the chi-square test to measure the effect of each variable.                    Overall it can be concluded that based on the results of the chi-square test using SPSS on the e-commerce variable obtained a chi-square value of 16,309 and a p-value of 0.001 0.05, so there is an influence between e-commerce variables on purchasing interest in vegetable products in Banda Aceh City. Furthermore, the measurement of the e-commerce variable indicators, namely system quality, information quality and service quality also uses square-test analysis, so that the results show that the quality of the system has a significant effect on buying interest of vegetable products, the quality of information has no significant effect on buying interest of Vegetable products and service quality have a significant effect on buying interest in vegetable products in Banda Aceh City.Keywords: E-commerce, Purchase interest.